Poverty Alleviation and profitability in Microfinance delivery: Is there a Conflict or Complementarity? - Jaabi, Seeku A. K. (Advances in Social Sciences Research Journal, 2018)
With a conspicuous absence of commercial banks in financing micro, small and medium enterprises, microfinance institutions (MFIs) emerged promising to finance growth and alleviate poverty by providing broad financial services to this vast market, thus expanding rural economic opportunities and reducing their vulnerabilities. MFIs have emerged to fill the crucial gap in banking this market niche in solving development problems of unemployment, poverty, income inequalities, enterprise growth, among others. Due to its socio-economic importance, enterprise finance has generated enormous enthusiasm among aid donors, governments and non-government organizations (NGOs) as an instrument for enhancing socio-economic development in a manner that is financially self-sustaining. The paper reports on a research which estimated the impact of microfinance institutions in The Gambia and selected MFIs in the developing world on poverty and other target variables, and attempted to relate such impact to the institutions’ design features. The findings showed that impact of lending on the recipient household’s income tend to increase, at a decreasing rate, as the recipient’s income and asset position improved, a relationship which can easily be explained in terms of the greater preference of the poor for consumption loans, their greater vulnerability to asset sales forced by adverse income shocks and their limited range of investment opportunities. There are significant outliers to this general pattern with very poor people not adequately reached as the programme focus on productive poor. This relationship defines an “impact frontier” which serves as a tradeoff: lenders can either focus their lending on the poorest and accept a relatively low total impact on household income, or alternatively focus on the productive poor and achieve higher impact. The position and slope of the estimated impact curve vary however with the policy and design of the institutions. Hence for many lending institutions the trade-off can often be moved by appropriate innovations in institutional design, in particular modifications to savings, loan collection, skills training and incentive arrangements for customers and employees. Building strategic partnerships with development agencies have over the years achieved complementarity in mist developing economies.